Magnetodeposited Nickel on Cu Substrate with the Angle Variation of Magnetic Field - Moh. Toifur; Effilia Allun Jaladri; Efi Kurniasari; Yuni Latifah; M. Taufiqurrahman (Universitas Ahmad Dahlan, 2022)
The performance of a thin layer of Cu/Ni as a cryogenic sensor is produced by electroplating at various angles with the aid of a 200G parallel magnetic field. Liquid nitrogen (LN2) is a low-temperature medium with temperatures varying from 0oC to -200oC. The characterization includes the sensor voltage range, sensor resistance, and sensor sensitivity. Thermocouple TCA-BTA -200oC to 1400oC is used as a temperature calibrator. The results showed that all sensors could measure the LN2 temperature in the range of 20oC to -200oC corresponds to the thermocouple's ability to measure up to -200oC. Each sensor has its advantages, but the sensor produced from coating each 3 minutes sample with an angle of 90o has the largest output voltage range up to 0.058 V, and the coating at an angle of 0o with the sensitivity level as a function of T is S(T) = 0.0051 - 0.002T, while the 3 minutes coating sensor with an angle of 60o has the smallest voltage range of 0.0439 V and sensitivity (1.88 ± 0.05) V/oC.